Implementation of TRIPs and Dynamics of Counterfeit Goods Trade in Southeast Asia: Regulations and Practices - Yunita, Primadiana; Killian, PM Erza (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Counterfeit goods refer to products that are illegally produced or distributed in violation of intellectual property rights (IPR), such as trademarks, designs, or patents. The trade-in counterfeit goods accounts for up to 10% of global trade and has impacts on global and local economies, including corporate losses, tax cuts, and barriers to innovation. This study uses neorealism theory to analyze the trade in counterfeit goods in Southeast Asia. The focus is on how countries prioritize domestic economic interests amidst pressures from the international system. Using a descriptive qualitative approach, this study explores the political, economic, and socio-cultural factors that support the trade in counterfeit goods, including the role of e-commerce and strategic relations with China. E-commerce accelerates the distribution of illegal goods, while China plays a major role as a producer. The results show that weak regional coordination, imbalances in state capabilities, and the ASEAN principle of non-intervention hinder the enforcement of IPR. To balance economic growth and IPR protection, innovative strategies are needed, such as strengthening national policies, cooperation between countries, and the use of technology in monitoring the trade in counterfeit goods.